2022
DOI: 10.1021/acsami.2c14087
|View full text |Cite
|
Sign up to set email alerts
|

3D Asymmetric Bilayer Garnet-Hybridized High-Energy-Density Lithium–Sulfur Batteries

Abstract: Lithium garnet Li 7 La 3 Zr 2 O 12 (LLZO), with high ionic conductivity and chemical stability against a Li metal anode, is considered one of the most promising solid electrolytes for lithium−sulfur batteries. However, an infinite charge time resulting in low capacity has been observed in Li−S cells using Ta-doped LLZO (Ta-LLZO) as a solid electrolyte. It was observed that this cell failure is correlated with lanthanum segregation to the surface of Ta-LLZO that reacts with a sulfur cathode. We demonstrated thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 57 publications
0
43
0
Order By: Relevance
“…Moreover, by simply reducing the dense layer thickness to our previously demonstrated 10 µ m , [ 22 ] we can project an energy density of 296 Wh kg −1 (924 Wh L −1 ), as indicated in Figure 3c,d. The energy density calculation approach was the same as our previous results [ 24 ] and can be found in Table S2 (Supporting Information). A comparison of our work with state‐of‐the‐art results for garnet Li–S cells is shown in Table S3 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, by simply reducing the dense layer thickness to our previously demonstrated 10 µ m , [ 22 ] we can project an energy density of 296 Wh kg −1 (924 Wh L −1 ), as indicated in Figure 3c,d. The energy density calculation approach was the same as our previous results [ 24 ] and can be found in Table S2 (Supporting Information). A comparison of our work with state‐of‐the‐art results for garnet Li–S cells is shown in Table S3 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[ 39,40 ] The amount of LiF increased for the 3 m GPE (Figure 4d) to nearly double the amount in 1 m GPE (Figure 4c). A peak ≈688.3 eV is attributed to decomposed FSI [ 24 ] and a peak ≈689.4 eV is attributed to fluorinated carbons. [ 39,40 ] The amount of fluorinated carbon in F 1s is significantly higher in 3 m GPE than in 1 m GPE, which is consistent with the results from C 1s spectra.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, development of garnet Li-S batteries has focused on use of flammable organic liquid, gel, and polymer catholytes to achieve stable cycling. ,,, For example our group has demonstrated stable hybridized garnet Li-S cells with ether-based liquid catholytes to provide good sulfur-cathode/LLZO interfacial contact in porous garnet trilayer (porous/dense/porous) LLZO architectures. , More recently using a bilayer (dense/porous) LLZO architecture, Shi et al demonstrated a high initial discharge capacity of 1307 mAh/g at 22 °C by using a poly­(ethylene oxide)-based interlayer on the cathode side and an ether-based catholyte. A gel polymer catholyte was later introduced to further stabilize the cell cycling performance at 22 °C, achieving 80% capacity retention over 265 cycles using sulfur in the form of sulfurized polyacrylonitrile (SPAN) . With these novel trilayer and bilayer LLZO architectures, applied pressure is not necessary for cell operation.…”
mentioning
confidence: 99%